On charge quantization and abelian gauge horizontal symmetries (1997)
ABSTRACT: Under the assumption that there exists a local gauge horizontal symmetry GH with allows only for a top quark mass at tree level, we look for the constraints that charge quatization and the family structure of the standard model imposes on that symmetry.